Influence of TIPS on laboratory and cardiac parameters in patients with Budd-Chiari Syndrome - Enaam Ali Al Mowafy; Mohamed Saber Hafez; Sally Waheed Elkhadry; Ahmed Elganzory; Ethar Mokhtar Badran; Zeinab M. Hefny (Egyptian Liver Journal)
Abstract Background and aims Transjugular intrahepatic portosystemic shunt (TIPS) is a commonly used method to treat Budd-Chiari syndrome (BCS). This study aimed to assess the immediate and mid-term changes in echocardiographic patterns and laboratory parameters post-TIPS and to determine the implications of these changes for patient management and prognosis. Methods From 2021 to 2023, a retrospective cohort study was conducted of BCS patients treated at Ain Shams University’s Tropical Medicine Department. About 23 patients underwent laboratory and echocardiographic follow-up examinations at baseline, one month, and six months following TIPS, including transthoracic echocardiograms and electrocardiograms. Results Post-TIPS, Blood Urea Nitrogen (BUN) levels decreased significantly from 14.16 ± 8.71 to 10.52 ± 5.66 (mg/dL post-TIPS (p = 0.007). Albumin levels modestly increased from 3.34 ± 0.85 to 3.36 ± 0.51 post-TIPS (p = 0.026), suggesting enhanced hepatic synthesis. Echocardiographically, the left atrial volume index (LAVI) increased from 21.91 ± 6.06 to 26.09 ± 5.39 (mL/m2) post-TIPS (p = 0.015). E velocity decreased from 40.35 ± 3.24 to 36.04 ± 7.3 (p = 0.031), and global longitudinal strain (GLS) showed improvement, reflecting adaptive cardiac responses to altered hemodynamics. Conclusion TIPS improved renal and hepatic function parameters. With respect to cardiac function, although changes in LAVI, E-velocity and GLS were mild and remained within the normal range but 6-month changes of GLS were positive showing an improvement by TIPS. So only a small number of patients with pathological cardiac conditions may need follow-up monitoring to identify and address potential complications at an early stage.